Changes of cortical activation in swallowing following high frequency repetitive transcranial magnetic stimulation in older adults - Park, J.‐W.; Sim, G.‐J.; Kim, H.‐J.; Yeo, J.‐S.; Hong, H.‐J.; Kwon, B. S. (Neurogastroenterology and motility, 2017)
Background This study explored whether high‐frequency repetitive transcranial magnetic stimulation (rTMS) can induce positive changes in the cortical areas of older adults who do not have functional difficulties in swallowing. Methods Ten healthy, right‐handed, elderly volunteers were subjected to 18F‐labeled fluorodeoxyglucose positron emission tomography(FDG‐PET) scans when at rest, swallowing before rTMS, and swallowing after rTMS. During the swallowing study, water was infused orally via a catheter at a rate of 600 mL/h. Subjects swallowed water every 20 seconds following a light flash for 30 minutes. During rest, the light source was active, but subjects were requested not to swallow. The rTMS consisted of 5 Hz applied to a pharyngeal motor hot spot in the right hemisphere for 10 minutes every weekday for 2 weeks. The intensity of the stimulation was set at 90% of the thenar motor threshold of the same hemisphere. The differences between each patient's active image and the control images (P<.05) on a voxel‐by‐voxel basis were examined to find significant increases in metabolism using statistical parametric mapping software. Key Results The cortical areas activated by swallowing before rTMS included the bilateral sensorimotor cortex (Brodmann's areas 3 and 4) and showed symmetry. The cortical areas activated by swallowing after rTMS were the same as the areas before rTMS. There was no statistical difference between the two swallowing activation areas. Conclusions and Inferences Older adults displayed the symmetry of cortical control of swallowing function. High frequency rTMS did not affect the activation in the swallowing sensorimotor cortices of elderly people. Older adults displayed the symmetry of cortical control of swallowing function. High frequency rTMS did not affect the activation in the swallowing sensorimotor cortices of elderly people.